Retroperitoneal Ganglioneuroma Encasing the Celiac and Superior Mesenteric Arteries - Justin K. Nelms; Eric K. Diner; Ernest E. Lack; Sunil V. Patel; Seyed R. Ghasemian; Mohan Verghese (The Scientific World Journal, 2004)
Ganglioneuroma is a rare neoplasm arising from the sympathoadrenal neuroendocrine system and has anatomic distribution paralleling the sympathetic chain ganglia and the adrenal medulla. In some cases, ganglioneuroma is the end stage maturation of less-differentiated neoplasms such as neuroblastoma or ganglioneuroblastoma, but based on age at diagnosis (over 10 years of age) and anatomic location, many of these tumors appear to arise de novo. It must be included in the differential diagnosis of posterior mediastinal and retroperitoneal mass. We report a case of retroperitoneal ganglioneuroma involving the celiac axis and superior mesenteric arteries in a 40-year-old female.